An Optoelectronic System for Measuring the Range of Motion in Healthy Volunteers: A Cross-Sectional Study - Medina-Mirapeix, Francesc (Medicina (Kaunas), 2019)
Background and Objectives: Within the clinical evaluation of multiple pathologies of the lower limb, the measurement of range of motion (ROM) of its joints is fundamental. To this end, there are various tools, from the goniometer as a reference to more recent devices such as inclinometry-based applications, photo capture applications, or motion capture systems. This study aimed to assess the validity, intra-rater, and inter-rater reliability of the VeloFlex system (VS), which is a new camera-based tool designed for tracking joint trajectories and measuring joint ROM. Materials and Methods: Thirty-five healthy volunteers (16 females; aged 18–61 years) participated in this study. All participants were assessed on two separate occasions, one week apart. During the first assessment session, measurements were obtained using a goniometer and the VS, whereas, in the second session, only the VS was used. In each assessment session, nine active movements were examined. For each movement, three trials were tested, and the mean of these three measures was used for analysis. To evaluate the concurrent validity and agreement, the Pearson correlation coefficient (r) and Bland-Altmann plots were used. Intra-rater and inter-rater reliability were evaluated using intra-class correlation (ICC), standard error of measurement (SEM), and minimal detectable change (MDC). Results: Both devices showed excellent correlations for all movements (r ranged from 0.992 to 0.999). The intra-rater reliability of the VS was excellent (ICC ranged from 0.93 to 0.99), SEMs ranged from 0.53% to 2.61% and the MDC ranged from 0.68° to 3.26°. The inter-rater reliability of the VS was also excellent (ICC ranged from 0.88 to 0.98), SEMs ranged from 0.81% to 4.76% and the MDC ranged from 2.27° to 4.42°. Conclusions: The VS is a valid and reliable tool for the measurement of ROM of lower limb joints in healthy subjects.